COMPARATIVE EFFICACY OF SOME NEONICOTINOIDS AND TRADITIONAL INSECTICIDES ON SUCKING INSECT PESTS AND THEIR NATURAL ENEMIES ON BT-121 COTTON CROP - S. Ahmed; 1M. S. Nisar; M. M. Shakir; M. Imran; K. Iqbal (Journal of Animal and Plant Sciences, 2014)
An experiment was conducted to determine efficacy of four neonicotinoids viz; nitenpyram 10SL, thiacloprid 480SC, imidacloprid 200SL, acetamaprid 20SL and four traditional insecticides such as profenofos 50EC, methidathion 40EC, bifenthrin 10EC, λ-cyhalothrin  2.5EC at their recommended field doses against sucking insect pests of cotton and their natural enemies on cotton variety Bt-121 at a farmers’ field in Multan. The data on post spray number of insect per leaf was taken to find difference among treatments. The results showed that nitenpyram, thiacloprid and imidacloprid were safer to natural enemies and toxic for the sucking pests as compared to conventional insecticides. The range of percent survival of the green lacewings (42.5-87.5 and 37.5-57.5), lady bird beetle (50.0-60.0 and 26.6-46.6) and pirate bug (28.0-60.0 and 24.0-57.0) was in neonicotinoids and conventional insecticide treated plots, respectively. The use of neonicotinoids for compatibility into integrated pest management is discussed.
Keywords: predators; OPs; pyrethroids; neonicotinoids; sucking insects; Bt cotton; field